Panagiotis Agrafiotis, Gema Casal, Gottfried Mandlburger, Karantzalos Konstantinos, Dimitrios Skarlatos - (:unkn) unknown (My University, 2026)
MDPI, Remote Sensing, Special Issue: Remote Sensing for Shallow and Deep Waters Mapping and Monitoring